Description of the male of Diphterocome peregovitsi Gyulai, G. Ronkay & L. Ronkay, 2014 (Lepidoptera, Noctuidae) - Volynkin, Anton V. (Zootaxa, 2018)
Diphterocome peregovitsi Gyulai, G. Ronkay & L. Ronkay, 2014 was recently described from North Vietnam basing on single female (Gyulai et al. 2014). It is a member of the Diphterocome chrysochlora species-complex, which includes nine species: D. chrysochlora (Hampson, 1898), D. thainympha Hreblay & Ronkay, 1999, D. nanlingi Gyulai, G. Ronkay & L. Ronkay, 2014, D. impectinata Hreblay, Peregovits & Ronkay, 1999, D. autumnalis (B.S. Chang, 1991), D. chloronympha Hreblay, Peregovits & Ronkay, 1999, D. nepalichlora Hreblay & Ronkay, 1999, D. thaumasia (Hreblay & Ronkay, 1998), and D. peregovitsi.